Flat Lenses Based on 2D Perovskite Nanosheets. Issue 30 (10th June 2020) - Wang, Ziyu; Yang, Tieshan; Zhang, Yupeng; Ou, Qingdong; Lin, Han; Zhang, Qianhui; Chen, Huanyang; Hoh, Hui Ying; Jia, Baohua; Bao, Qiaoliang
Abstract: Ultrathin flat lenses based on metasurfaces or metamaterials have shown great promise in recent years as essential components in nano‐optical system, with capability of abrupt changes of light wavefronts. However, such structural designs require complex nanopatterns and a time‐consuming nanofabrication process. In this regard, flat lenses are developed based on 2D perovskite nanosheets, using a cost‐effective mask‐free femtosecond direct laser writing system. The optical properties of the 2D perovskite are rationally adjusted through facile composition engineering as well as thickness‐dependent quantum‐size confinement. A diffraction theory model is derived to understand the focusing mechanism of the 2D perovskite nanosheets flat lenses. The as‐fabricated lenses exploit the tunable material property variations to effectively manipulate not only the amplitude but also the phase of the incident light to focus into a 3D focal spot with a sub‐wavelength resolution in the range of 0.5–0.9λ. The results pave the way toward low‐cost and large‐scale high‐resolution imaging applications in the future. Abstract : Flat lenses based on 2D perovskite nanosheets with a subwavelength focusing capability (≈0.5λ) are reported. These lenses are fabricated by using a cost‐effective mask‐free femtosecond direct laser writing system. Halide elemental substitution may further reveal potential tunable focus capability (0.5–0.9λ).